The Asset Redeployability Channel: How Uncertainty Affects Corporate Investment - Kim, Hyunseob; Kung, Howard (Review of Financial Studies, 2017)
This paper examines how uncertainty affects corporate investment under varying degrees of asset redeployability. We develop new measures of asset redeployability by accounting for the usability of assets within and across industries. We identify plausibly exogenous shocks to economic uncertainty by using major economic and political events. We find that after an increase in uncertainty, firms using less redeployable capital reduce investment more. More redeployable assets exhibit higher recovery rates and are traded more actively in secondary markets. Overall, our results suggest that frictions in redeploying assets affect liquidation values and therefore make firms cautious about investment decisions under uncertainty. Received August 29, 2014; accepted July 13, 2016, by Editor Itay Goldstein.